Supratentorial ependymoma with YAP1:FAM118B fusion: A case report. Issue 2 (22nd January 2021) - Wang, Jian; Wang, Liang; Fu, Lin; Li, Qing‐Chang; Qiu, Xue‐Shan; Wang, En‐Hua; Yu, Juan‐Han
Abstract : We report a case of a 26‐year‐old Chinese man who had experienced three grand mal seizures in the past two months. Magnetic resonance imaging revealed a relatively well‐circumscribed lesion in the left frontal lobe. A craniotomy with total excision of the tumor was performed. Histopathological investigations confirmed a grade 2 ependymoma according to the World Health Organization classification. Genetic analysis revealed a tumor harboring FAM118B fusion to YAP1, and no other genetic alterations or methylation of the O 6 ‐methylguanine‐DNA methyltransferase gene promoter were detected. This is the second case report of ependymoma with YAP1:FAM118B fusion.